2016
DOI: 10.18805/ijar.9644
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of peste des petitis ruminants in sheep and goats atSalem district of Tamil Nadu, India

Abstract: An unknown disease outbreak was reported in four villages of Salem district viz., Aranganoor, Athigaripatty, Avadathur and Amanikondalanpatty in Tamil Nadu State and subsequent mortality among the Mecheri breed of sheep and Tellichery breed of goat was investigated. The clinical signs observed among the animals were high fever, anorexia, profuse diarrhoea with bilateral mucopurulent oculonasal discharge. Bran like necrotic ulcers in the mucosa of oral cavity, tongue, dental pad was seen on necropsy. Samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…Pathomorphology of Concurrent Peste des Petits Ruminants (PPR) and Contagious Caprine Pleuropneumonia (CCPP) in a Cross ... Out of 45 goats at risk, 23 showed clinical signs and 17 died of diseases with morbidity, mortality and case fatality rate of 51.11%, 37.77% and 73.91% respectively. In the present outbreak, high mortality was noticed as compared to previous records of 17.4% (Manimaran et al, 2017) and 13.4% (Kumar et al, 2014) during a natural outbreak of PPR in goats. Higher morbidity and mortality in the present study might be due to concurrent infection of CCPP and intensive system of management which facilitated the close contact and rapid spread of infection between the animals.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Pathomorphology of Concurrent Peste des Petits Ruminants (PPR) and Contagious Caprine Pleuropneumonia (CCPP) in a Cross ... Out of 45 goats at risk, 23 showed clinical signs and 17 died of diseases with morbidity, mortality and case fatality rate of 51.11%, 37.77% and 73.91% respectively. In the present outbreak, high mortality was noticed as compared to previous records of 17.4% (Manimaran et al, 2017) and 13.4% (Kumar et al, 2014) during a natural outbreak of PPR in goats. Higher morbidity and mortality in the present study might be due to concurrent infection of CCPP and intensive system of management which facilitated the close contact and rapid spread of infection between the animals.…”
Section: Resultscontrasting
confidence: 57%
“…Spleen and lymph node showed variable degrees of lymphoid cell depletion. Degenerative and necrotic changes were noticed in liver and kidney (Abraham et al, 2015;Manimaran et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Necropsy was conducted only in 43 (25.44%) animals comprising 32 goats and 11 numbers of sheep due to field of inflammatory cells in the sub-mucosa of villi as well as muscle layer of intestine along with depletion of splenic pulp and congestion. Microscopic changes observed were in agreement with Jagtap et al (2012) and Manimaran et al (2017).…”
Section: Gross and Histopathologysupporting
confidence: 79%
“…There was history of inter-state migration of animals as well as purchasing of small ruminants from local markets near the border areas in all outbreaks which may be regarded as a possible contributing factor for field outbreaks (Kumar et al 2001) Epidemiology, Haemato-biochemical and Pathological Changes Related to Field Outbreaks of PPR in Small Ruminants in Odisha on skin (11.76%) with different degree of severity in affected small ruminants. Clinical signs as reported were consistent with Nath et al (2014) and Manimaran et al (2017). There was salivation with fibrinous exudates and erosive lesions on tongue, hard palate, gums, lips as well as yellowish necrotic crusts in oral commissures.…”
Section: Epidemiologysupporting
confidence: 69%
“…Peste des petits ruminant (PPR) or Pseudo Rinderpest, which literally means Plague of small ruminants is an economically significant disease of sheep and goats. The disease is highly contagious in nature, and is clinically characterized by stomatitis-pneumo-enteritis complex in which morbidity reported is as high as 100 per cent and mortality reaches upto 90 per cent (Manimaran et al, 2017). Kataria et al, (2007) reported a case fatality rate of 70 per cent in sheep and 80 per cent in goats in Haryana, India.…”
Section: Introductionmentioning
confidence: 99%